2022
DOI: 10.1038/s41598-022-18242-4
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-to-lymphocyte ratio predicts short-term mortality in patients with moderate to severe traumatic brain injury

Abstract: An easily accessible biomarker with good diagnostic power for patients with traumatic brain injury (TBI) was needed to predict the short-term mortality. Studies have shown that platelet-to-lymphocyte ratio (PLR) is a biomarker for patients with tumor. This study aimed to identify the relationship between PLR and short-term mortality in patients with moderate to severe TBI. This is a retrospective cohort study. We selected patients with moderate to severe TBI who were admitted to the emergency department of The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…A retrospective study by Li and Deng (2022) in 170 patients with moderate-to-severe TBI assessed the prognostic ability of the PLR and Rotterdam computed tomography score on the patients' mortality rate. It was found that PLR can be an independent biomarker with a good level of prognostic ability in short-term mortality (30-day mortality), with hazard risk = 1.523 (95% confidence interval [CI] 1.110-2.090, P = 0.009) and area under the curve (AUC) 0.711 (95% CI 0.618-0.803, P < 0.001).…”
Section: Results Of Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective study by Li and Deng (2022) in 170 patients with moderate-to-severe TBI assessed the prognostic ability of the PLR and Rotterdam computed tomography score on the patients' mortality rate. It was found that PLR can be an independent biomarker with a good level of prognostic ability in short-term mortality (30-day mortality), with hazard risk = 1.523 (95% confidence interval [CI] 1.110-2.090, P = 0.009) and area under the curve (AUC) 0.711 (95% CI 0.618-0.803, P < 0.001).…”
Section: Results Of Synthesismentioning
confidence: 99%
“…[3,31] At sites of injury, damaged cells release factors that trigger the inflammatory cascade, along with chemokines and growth factors, which will attract neutrophils, monocytes, lymphocytes, and mast cells to the injury site. [14,25] Studies have demonstrated that a considerable number of indicators may be found in cerebrospinal fluid after TBI, indicating that neuroinflammation is one of the key causes of subsequent damage in TBI. e identification of these markers, however, has a high technological and financial need.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have shown contradicting perspectives of a negative association between higher PLR and worse outcomes. An observational study (n = 170) reported that lower PLR could be an independent factor for higher survival in patients with traumatic brain injury [41]. That phenomenon explains that spontaneous aggregation and excessive platelet consumption after brain injury induce platelet depletion, thereby breaking the balance of coagulation and anticoagulation, enhancing bleeding risk.…”
Section: Discussionmentioning
confidence: 99%
“…It has been identified as a prognostic predictor in patients with cancer, cardiovascular diseases, pulmonary diseases, and sepsis [ 8 - 11 ]. Trauma-related research has reported the utility of PLR as a prognostic predictor for organ damage, such as abdominal trauma and brain injury [ 12 , 13 ]. A significant correlation between PLR and patient prognosis for the aforementioned diseases and trauma has been reported.…”
Section: Introductionmentioning
confidence: 99%